RESISTENSI PESANTREN PADA MASA PENJAJAHAN BELANDA - Moh. Irnawan Jauhari (Universitas Islam Lamongan, 2017)
Pesantren (Islamic boarding school) is an educational institution long standing in Nusantara (Java), besides what the so-called surau in Sumatra. In the course of its development, its traces and existence are still present and could be seen today. In the transition between Hinduism-Buddhism to Islam, the role of pesantren was very important in guarding the emerging shift. Similarly, during the era of colonization by the Europeans, Pesantren could still find its footing as a religious and cultural based institution. Although the Dutch eventually made counter-educational institutions with their existing curriculum, in fact the existence of pesantren remained strong. Based on the dialectic, the combination of pesantren system and curriculum emerged. Pesantren also fought the spirit of struggle to its santri to see that the struggle is not solely determined by forces alone. And the most secure and strategic path is through education.Keywords: Pesantren, Resistance, Colonization.